Steep repolarization time gradients in pig hearts cause distinct changes in composite electrocardiographic T‐wave parameters - Jeanne van derWaal; Laura Bear; Veronique Meijborg; Rémi Dubois; Matthijs Cluitmans; Ruben Coronel (Annals of Noninvasive Electrocardiology, 2022)
Abstract Background The T wave of the electrocardiogram (ECG) reflects ventricular repolarization. Repolarization heterogeneity is associated with reentrant arrhythmias. Several T‐wave markers (including QT interval) have been associated with ventricular arrhythmias, but studies linking such markers to underlying local repolarization time (RT) inhomogeneities are lacking. We aimed to investigate the relation of several T‐wave markers to controlled drug‐induced regional RT gradients in intact pig hearts. Methods Repolarization time gradients were created by regional infusion of dofetilide and pinacidil in four atrially paced porcine Langendorff‐perfused hearts placed inside a torso tank. From the 12‐lead ECG on the torso tank, the mean, maximum, and dispersion (max–min) of QTtime, JTtime, Tpeak–end, Twidth, TQratio, dV/dtmax, Tarea, Tamp, and T‐upslope duration were determined, as well as upslope end difference between leads V1 and V6. Results Temporal T‐wave parameters Tpeak–end, Twidth, and TQratio show a significant and high correlation with RT gradient, best reflected by mean value. Tarea (mean, max and dispersion) and dV/dtmax dispersion show only a moderate significant correlation. T‐upslope duration shows a significant correlation in particular for mean values. Mean, maximum, or dispersion of QTtime and V1–V6 upslope end difference were not significantly correlated with RT gradient. Conclusion Composite 12‐lead ECG T‐wave parameters Tpeak–end, Twidth, TQratio, upslope duration, and Tarea show a good correlation with underlying RT heterogeneity, whereas standard clinical metrics such as QTtime do not reflect local RT heterogeneity. The composite T‐wave metrics may thus provide better insights in arrhythmia susceptibility than traditional QTtime metrics.